CCAFS village baseline study - implementation manual - Förch, Wiebke; Barahona, Carlos; Kristjanson, Patricia M.; Thornton, Philip K.; Mango, Joash; Onyango, Leah; Noor F (2011)
This implementation manual is to be used in conjunction with the step-by-step guide, as well as the templates for the debriefing document and the site analysis report. In the first half of 2011, CCAFS will undertake village-level baseline studies at 14 initial CCAFS sites in Eastern Africa, West Africa and the Indo-Gangetic Plains. These will supplement the quantitative household baseline surveys that were conducted in 2010, and will be a first step towards local engagement for participatory action research. The village baseline study aims to provide baseline information at the village level about some basic indicators of natural resource utilisation, organisational landscape, information networks for weather and agricultural information, as well as mitigation baseline information, which can be compared across sites and monitored over time. The village baseline aims to capture some of the diversity in the landscape, across villages. We are aiming for sufficient precision in some of these indicators to capture changes that occur. The same study will be carried out in very diverse locations, thus it is not intended to go into depth and explore complex relationships; the intention is that these will be explored in further research in the same locations.